Reduced blood‐brain barrier expression of fatty acid‐binding protein 5 is associated with increased vulnerability of APP/PS1 mice to cognitive deficits from low omega‐3 fatty acid diets. Issue 1 (18th December 2017) - Pan, Yijun; Choy, Kwok H. C.; Marriott, Philip J.; Chai, Siew Y.; Scanlon, Martin J.; Porter, Christopher J. H.; Short, Jennifer L.; Nicolazzo, Joseph A.
Abstract : Lower levels of the cognitively beneficial docosahexaenoic acid (DHA) are often observed in Alzheimer's disease (AD) brains. Brain DHA levels are regulated by the blood‐brain barrier (BBB) transport of plasma‐derived DHA, a process facilitated by fatty acid‐binding protein 5 (FABP5). This study reports a 42.1 ± 12.6% decrease in the BBB transport of 14 C‐DHA in 8‐month‐old AD transgenic mice (APPswe, PSEN1∆E9) relative to wild‐type mice, associated with a 34.5 ± 6.7% reduction in FABP5 expression in isolated brain capillaries of AD mice. Furthermore, short‐term spatial and recognition memory deficits were observed in AD mice on a 6‐month n‐3 fatty acid‐depleted diet, but not in AD mice on control diet. This intervention led to a dramatic reduction (41.5 ± 11.9%) of brain DHA levels in AD mice. This study demonstrates FABP5 deficiency and impaired DHA transport at the BBB are associated with increased vulnerability to cognitive deficits in mice fed an n‐3 fatty acid‐depleted diet, in line with our previous studies demonstrating a crucial role of FABP5 in BBB transport of DHA and cognitive function. Abstract : Docosahexaenoic acid (DHA), an omega‐3 fatty acid essential for cognitive function, is transported by fatty acid‐binding protein 5 (FABP5) at the blood‐brain barrier (BBB) into the brain. In this study, lower BBB expression of FABP5 was identified in transgenic Alzheimer's disease (AD) mice, making them more vulnerable to DHA dietary depletion, with AD mice fed an omega‐3 depleted diet demonstrating exacerbated cognitive impairment.